LEARNER FEEDBACK TO THE INITIAL TEACHER EDUCATOR’S EAP TEACHING: A REFLECTIVE STUDY (IAIN Syekh Nurjati Cirebon, 2022)
While the success of language instruction is unquestionably reflected in students’ performance in communicating in the target language, their voices generally can best express their success, disappointment, or complacency worth to reflect. This article, based on the study held at Universitas Negeri Yogyakarta in 2021, reports on a mixed-methods investigation that examines how an initial teacher educator (ITE) manages a course in English for academic purposes (EAP) from students’ perspectives. Fifty-five sociology education students selected through convenience sampling participated in a quantitative survey and focus group discussion. The quantitative data analysis shows students' positive views regarding the initial teacher educator's general performance, delivery, time management, material, media, assessment, and care. To complement the quantitative findings, the qualitative data scrutinized through thematic analysis suggest three imperative measures for more effective EAP instruction. Even though students rated ITEs performance as